Monitoring job offer decisions, punishments, exit to work, and job quality - Gerard J. van den Berg; Johan Vikström (Institute for the Study of Labor (IZA), 2009)
Unemployment insurance systems include monitoring of unemployed workers and punitive sanctions if job search requirements are violated. We analyze the effect of sanctions on the ensuing job quality, notably on wage rates and hours worked, and we examine how often a sanction leads to a lower occupational level. The data cover the Swedish population over 1999-2004. We estimate duration models dealing with selection on unobservables. We use weighted exogenous sampling maximum likelihood to deal with the fact the data register is large whereas observed punishments are rare. We also develop a theoretical job search model with monitoring of job offer rejection vis-a-vis monitoring of job search effort. The observation window includes a policy change in which the punishment severity was reduced. We find that the hourly wage and the number of hours are on average lower after a sanction, and that individuals move more often to a lower occupational level, incurring human capital losses. Monitoring offer rejections is less effective than monitoring search effort.
urn:nbn:de:101:1-20090825646
Keywords: J64; C41; C21; J31; J44; J65; J62; 330; Unemployment; duration; sanction; wage; hours worked; weighted exogenous sampling maximum likelihood; case worker; job offer; offer rejection; search effort; Arbeitsmarktpolitik; Arbeitsplatzsuchmodell; Anspruchslohn; Arbeitsverhältnis; Schweden